마늘 유전자원의 Stemphylium vesicarium에 의한 잎마름병 저항성 평가 - 이진주(Jin Ju Lee); 한지원(JiWon Han); 김헌(Hun Kim); 김진철(Jin-Cheol Kim); 최경자(Gyung Ja Choi) (Sigmulbyeong yeon'gu, 2024)
Leaf blight caused by Stemphylium vesicarium is one of the most important fungal diseases of garlic (Allium sativum L.) worldwide, which results in a reduction of quality and yield. The breeding of resistant cultivars is an efficient approach to decrease the use of chemical fungicides and minimize crop losses. In this study, to find the resistant garlic resources against S. vesicarium, we evaluated the resistance degree of 20 garlic germplasms. To do this, garlic seedlings at four-leaf stage were rubbed with nonabsorbent cotton and then inoculated with spore suspension (3.0×105 spores/ml of potato dextrose broth) of S. vesicarium by spray method. Three to seven days after inoculation, the infected leaf area (%) of garlic seedling was measured. 'Daeseo' and 'Namdo' were included as susceptible and resistant control cultivars, respectively. After 3 to 7 days of incubation, the infected leaf area (%) of garlic seedling was measured. Our results showed that IT245512, IT245528, and IT244068 lines exhibited the highest resistance against S. vesicarium, whereas IT257134 and IT253043 lines were more susceptible than the susceptible cultivar 'Daeseo'. Based on the results, the resistant genetic resources selected in this study can be used a basic material for resistant garlic breeding system against leaf blight. Stemphylium vesicarium에 의해 발병하는 잎마름병은 마늘재배에 있어 전 세계적으로 가장 중요한 곰팡이 병 중 하나이며, 종자의 품질과 수확량을 감소시킨다. 병 저항성 품종의 재배는 화학 농약의 사용을 감소시키고, 작물 손실을 최소화하는 데 효율적인 방법이다. 본 연구는 잎마름병 저항성 마늘 유전자원을 발굴하기 위하여, 20점의 마늘 유전자원의 잎마름병에 대한 저항성을 조사하기 위하여 실험하였다. 온실에서 재배한 4엽기 유묘의 잎을, 접종 직전에 탈지하지 않은 비흡수성 재질의 솜으로 문지른 후에 멸균한 1/2 농도의 PDB 용액으로 수확한 S. vesicarium KACC 44530 균주의 포자현탁액(3.0×105 spores/ml)을 분무하여 접종하였다. 그리고 접종 3-7일 후에 잎에 발생한 잎마름병의 병반면적률(%)을 조사하였다. 이때 저항성 및 감수성 대조 품종으로 '남도'와 '대서' 마늘이 사용되었다. 실험한 유전자원 중에서, IT245512, IT245528 및 IT244068은 잎마름병에 가장 높은 저항성을 보였으며, 유전자원 IT257134와 IT253043은 잎마름병에 대하여 가장 높은 감수성을 나타내었다. 본 연구에서 선발한 저항성 유전자원은 잎마름병 저항성 육종 시스템에 유용한 자원으로 이용될 수 있을 것이다.